Remnant cholesterol and mild cognitive impairment: A cross-sectional study - Zhang, Qiaoyang; Huang, Shan; Cao, Yin; Dong, Guanzhong; Chen, Yun; Zhu, Xuanyan; Yun, Wenwei; Zhang, Min (Frontiers in Aging Neuroscience, 2023)
Abstract: Objective: Emerging evidence suggests that elevated remnant cholesterol (RC) correlates with several health conditions. To explore the association of plasma RC with MCI incidence and the relationship between plasma RC and different domains of cognition in MCI patients. Methods: 36 MCI patients and 38 cognitively healthy controls (HC) were enrolled in the present cross-sectional study. Using total cholesterol (TC) minus high-density lipoprotein cholesterol (HDL-C) minus low-density lipoprotein cholesterol (LDL-C) as the formula for calculating fasting RC. Cognition was assessed using the Chinese version of the Montreal cognitive assessment (MoCA), Auditory Verbal Learning Test (AVLT), Digit Symbol Substitution Test (DSST), Trail Making Test (TMT), and Rey-Osterrieth Complex Figure Test (ROCF). Results: Compared to healthy controls, MCI patients had a higher level of RC, the median difference in RC levels between these two groups was 8.13 mg/dL (95.0%CI: 0.97-16.1). Concurrently, plasma RC level was positively associated with MCI risk (OR=1.05, 95%CI: 1.01-1.10). Notably, elevated RC level was correlated with impaired cognition in MCI patients, such as DSST (pr=-0.45, p=0.008), ROCF- Long Delayed Recall (pr=-0.45, p=0.008), AVLT-Immediate Recall (pr=-0.38, p=0.028), and TMT-A (pr=0.44, p=0.009). Conversely, no significant correlation was found between RC and the AVLT-Long Delayed Recall test. Conclusion: This study found that plasma remnant cholesterol was associated with MCI. Further large longitudinal studies are needed in the future to confirm the results and clarify the cause-and-effect relationship.